Languages of Difference in the Early Modern Portuguese Empire. The Spread of “Caste” in the Indian World - Xavier, Ângela Barreto (2016)
This essay discusses the circulation of the language of caste in the Indian world in the context of the Portuguese empire. Caste is an inevitable word in the moment of considering the Indian social system, as well as to compare it with European/Western societies. Since it was a word initially brought by the Portuguese to the Indian world, it is relevant to ask whether the Portuguese played an important role in its transformation into such a relevant social category. Six of the most important sixteenth-century narratives about the Portuguese presence in India, as well as treatises, letters, legal documents, vocabularies and dictionaries of the early-modern period will be under scrutiny in order to identify the variations of the word “casta”, its circulation in Estado da Índia, and beyond it. The analysis of these sources will also permit to understand how Portuguese colonial experience shaped the future meanings of “casta”, and therefore, the ways “casta” shaped Indian society (and not only).